Analisis Kebijakan Anggaran Berbasis Akreditasi di Institut Agama Islam Negeri Kendari - Sulaiman, Nasrullah (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2024)
This policy paper describes the problem of accreditation-based budget policy at IAIN Kendari, namely that universities are faced with pressure to improve quality and competitiveness, including through increasing the accreditation of study programs and institutions. Meanwhile, budget managementthat focuses on accreditation is an important strategy to support these efforts. By carefully allocating resources to support activities that support the achievement of accreditation standards, universities can ensure the efficient and effective use of their funds. This article uses a qualitative method with a literature study approach, where the author refers extensively to existing primary and secondary data and sources. The results show that the main challenge in accreditation-based budget management at IAIN Kendari is the lack of a regulatory framework that regulates the budget proposal process oriented towards increasing accreditation. Without clear guidance, the allocation of funds to support increased accreditation can be undirected and less effective. Thus, the author recommends that to ensure the success of an accreditation-based budget management policy, concrete steps are needed, such as synergy with the institution's main performance indicators, making clear regulations, active involvement of Quality Assurance Institutions, increasing awareness and training, as well as ongoing monitoring and evaluation.